Recommendation for the use of respiratory syncytial virus vaccines - Ping-Ing Lee; Yhu-Chering Huang; Ching-Chuan Liu; Shee-Uan Chen; Po-Ren Hsueh; Shih-Chi Ku; Po-Yen Chen; Chih-Jung Chen; Yi-Tsung Lin; Chun-Yi Lu; Nan-Chang Chiu; Hsin Chi; et al. (Journal of Microbiology, Immunology and Infection)
Respiratory syncytial virus (RSV) is the most common pathogen for young children hospitalized with bronchiolitis and pneumonia. Most infections occur below 1 year of age. RSV is also a significant viral pathogen for adults with respiratory tract infection.Vaccines targeting the pre-fusion protein of RSV, including recombinant and mRNA vaccines, are now available. A committee of experts from related fields was convened by the Taiwan Immunization Vision and Strategy to develop recommendations for RSV vaccination in the elderly and pregnant women.The recommendation is not intended as a sole source of guidance in the prevention of RSV infection in children. The provisions listed in this recommendation are comprehensive suggestions made by experts in Taiwan based on existing medical evidence. This recommendation should be subject to modification in light of additional medical research findings in the future, and these provisions should not be cited as a basis for dispute resolution.